Opportunities and Challenges of Islamic Education in the Digital Era - Miftachul Huda; Abd Hadi Borham; Muhammad Iqbal Dewantara (Ar-Fachruddin: Pendidikan Agama Islam, 2024)
The purpose this research is to analyze the opportunities and challenges of Islamic education in the era of digital technology. Within the transformation of Islamic education, challenges and opportunities in the 21st century. This literature review identifies relevant literature sources on Islamic education in the digital era, conducts critical analysis of selected content, and organizes information thematically. The research aims to understand challenges such as changes in educational paradigms and technology integration, as well as opportunities such as broader access to learning resources and the use of digital media in Islamic education. The results of this research are expected to contribute to the development of adaptive education strategies and policies for the digital era. The findings of this work indicate that the role of digital technology in Islamic education in the 21st century requires a mature approach based on the concept of digital literacy to address challenges and enrich religious learning experiences. Islamic education in the digital era faces challenges of authenticity and accessibility, but offers global opportunities and interactive learning methods by developing digital literacy, ethics in technology use, and applying relevant theories.